PANDANGAN MASYARAKAT JAWA TERHADAP LARANGAN MENIKAH PADA BULAN MUHARRAM PERSPEKTIF HUKUM ISLAM (Studi Kasus di Desa Bulurejo Kecamatan Diwek Kabupaten Jombang) - Irtiyaj Dwi Lestari; Masrokhin Masrokhin (JURNAL ILMIAH NUSANTARA, 2024)
The implementation of a wedding cannot be separated from the traditions or customs that apply in an area. Among the people of Bulurejo Village, Diwek District, Jombang Regency, there is a belief that they do not dare to carry out weddings in the month of Suro or the month of Muharram in the Hijriyah calendar. Because that month is believed by the Javanese people of Bulurejo Village to be a bad month. This research has the following objectives: First, to find out the views of the Javanese people of Bulurejo village towards weddings in the month of Suro or Muharram. Second, to find out the Islamic law review of the tradition of prohibiting marriage in the month of Muahrram. This research uses a normative research type method and a qualitative approach. Then the way researchers obtain data in the field is through interviews and documentation. The research results concluded that according to the views of the Javanese people in Bulurejo Village regarding the prohibition on marriage during the month of Muharram, people should be more careful in carrying out things or things related to worship, by straightening out their intentions or returning their intentions or returning everything to Allah alone. . The public must be aware that customary law is a product of humans themselves, while Allah's law is a provision that comes from Allah, so that customary law cannot be used to solve problems. In applying Islamic law, it must prioritize the benefit of the people, as stated in the 'urf theory, so This needs to be studied more deeply so that it will not cause confusion among Muslims, especially Javanese Muslim communities who will hold weddings in the month of Suro/Muharram.